Structure of the low-affinity penicillin-binding protein 5 PBP5fm in wild-type and highly penicillin-resistant strains of Enterococcus faecium. - Zorzi, W (1996)
Among its penicillin-binding proteins (PBPs), Enterococcus faecium possesses a low-affinity PBP5, PBP5fm, which is the main target involved in beta-lactam resistance. A 7.7-kb EcoRI chromosomal fragment of E. faecium D63r containing the pbp5fm gene was cloned and sequenced. Two open reading frames (ORFs) were found. A 2,037-bp ORF encoded the deduced 73.8-kDa PBP5fm, the amino acid sequences of which were, respectively, 99.8, 78.5, and 62% homologous to those of the low-affinity plasmid-encoded PBP3r of Enterococcus hirae S185r and the chromosome-encoded PBP5 of E. hirae R40 and Enterococcus faecalis 56R. A second 597-bp ORF, designated psrfm, was found 2.3 kb upstream of pbp5fm. It appeared to be 285 bp shorter than and 74% homologous with the regulatory gene psr of E. hirae ATCC 9790. Different clinical isolates of E. faecium, for which a wide range of benzylpenicillin MICs were observed, showed that the increases in MICs were related to two mechanisms. For some strains of intermediate resistance (MICs of 16 to 64 micrograms/ml), the increased level of resistance could be explained by the presence of larger quantities of PBP5fm which had an affinity for benzylpenicillin (second-order rate constant of protein acylation [k+2/K] values of 17 to 25 M(-1) s(-1)) that remained unchanged. For the two most highly resistant strains, EFM-1 (MIC, 90 micrograms/ml) and H80721 (MIC, 512 micrograms/ml), the resistance was related to different amino acid substitutions yielding very-low-affinity PBP5fm variants (k+2/K < or = 1.5 M(-1) s(-1)) which were synthesized in small quantities. More specifically, it appeared, with a three-dimensional model of the C-terminal domain of PBP5fm, that the substitutions of Met-485, located in the third position after the conserved SDN triad, by Thr in EFM-1 and by Ala in H80721 were the most likely cause of the decreasing affinity of PBP5fm observed in these strains.